Pengembangan Media Flashcard Penjumlahan Berbasis Canva Untuk Melatih Kemampuan Berhitung Di Kelas II SD Negeri 101746â€ Klumpang Kebun Tahun Ajaran 2023/2024 - Hadisty Shakira Aulia; Astria Ayu Ramadianti; Nuri Ramadhan (Universitas Muria Kudus, 2025)
This research aims as follows: (1) to determine the feasibility of the flashcard media developed in training students' numeracy skills in class II of SD Negeri 101746 Klumpang Kebun, (2) to find out about the effectiveness of students in class II of SD Negeri 101746 Klumpang Kebun after using flashcard media. This type of research is Research & Development (R & D) with the ADDIE research and development model. The subjects of this research were class II students at SD Negeri 101746 Klumpang Kebun, totaling 28 students, consisting of 14 male students and 14 female students. This research was carried out by carrying out learning using flashcard media and then distributing student response questionnaires. The results of research on media validator analysis showed that the presentation reached 91% which was categorized as very feasible and material validator analysis showed that the average presentation reached %. The distribution of student response questionnaires showed that the average presentation reached 88% which was categorized as very effective. Based on the research results, it can be seen that flashcard media is very feasible and very effective.